XX CONFERENCE OF THE PARTS OF LIMA AND THE URGENCY OF DECISIONS ON CLIMATE CHANGE - Macines Romero, Rogelio Nicolás (2014)
One of the major global problems facing the United Nations is climate change. Since the 90s of last cen-tury, there is the conviction that must change the socio- economic development model to one that is friendlier to the environment; but for this there must be a consensus among nations to make it happen. While there has been progress with the implementa-tion of the Kyoto Protocol in the sense of achieving a binding agreement, no progress has been made by the existence of different positions in the negotiations. That is why, in December 2014 will be held in Lima the XX Conference of the Parties in order to prepare a draft agreements to be discussed and approved at COP 21 to be held next year in Paris.The present article aims to analyze the context in which they are in a while doing these conferences and identify the difficulties in negotiations for an agreement to avoid increasing the potential damage that humanity would suffer in the future. As mentioned in the title, no urgency to make decisions being the requirement of the most vulnerable parts.